PROFESSIONAL EXAMINATION. - Chamberlain, Henry T.; Graham, Willard J. (The Accounting Review, 1958)
This article presents some problems prepared by the Board of Examiners of the American Institute of Certified Public Accountants, which were presented as the second half of the examination in accounting practice on November 7, 1957. The candidates were required to solve problem 1 and any three of the remaining four problems. The total weight assigned to this section of the examination was 50 points and the examiners point out that the suggested time allowances are approximately proportional to the point value of the various problems. The suggested time allowances for the problems were as follows: Problem 1, 30 to 45 minutes; any three of the remaining four problems, 150 to 225 minutes. The problem 1 asked the students to prepare a work sheet showing details of the computation of the corporate Federal income tax for the fiscal year ended May 31, 1957 of Taxpayer Manufacturing Corp. In another problem, the trial balance sheet of Pacific Import Co. has been provided to students and they were asked to prepare a columnar worksheet for the company and its branch with columns for "Trial balance," "Adjustments and eliminations" and "Branch income statement."